Nicotine delivery and relief of craving after consumption of European JUUL e-cigarettes prior and after pod modification - Nadja Mallock (Nature Portfolio, 2021)
Abstract The emergence of e-cigarettes on the consumer market led to a tremendous rise in e-cigarette consumption among adolescents in the United States. The success of JUUL and other pod systems was linked to its high nicotine delivery capacity. In compliance with the European Tobacco Product directive, liquid nicotine contents in the European JUUL variants are limited to 20 mg/mL or below. A short time after launching the initial version in Europe, JUUL pods have been modified in terms of the wick material used. This modification has been demonstrated previously to lead to an elevated aerosol generation, consequently, to a larger amount of nicotine per puff generated. The present study was designed to assess whether the mentioned differences between the “initial” and “modified” JUUL versions may cause a significant difference during consumption, and how nicotine delivery compares with tobacco cigarettes. In this single-center three-arm study, nicotine pharmacokinetics and influence on urge to smoke/vape were compared for tobacco cigarettes, the “initial” version of the European JUUL, and the “modified” version of the European JUUL. Participants, 15 active smokers and 17 active e-cigarette users, were instructed to consume their study product according to a pre-directed puffing protocol. Venous blood was sampled for nicotine analysis to cover the acute phase and the first 30 min after starting. Nicotine delivery and the reduction of urge to smoke/vape upon usage of both European JUUL variants were lower in comparison to tobacco cigarettes. This suggests a lower addictive potential. Modification of the pod design did not result in significant differences at the first ten puffs, as confirmed by a vaping machine experiment. Apparently, the limitations by the initially used wick material only come into effect after longer usage time.